2023
DOI: 10.1177/17562848231174277
|View full text |Cite
|
Sign up to set email alerts
|

Safety of fecal microbiota, live-jslm (REBYOTA) in individuals with recurrentClostridioides difficileinfection: data from five prospective clinical trials

Abstract: Background: Microbiota-based treatments reduce the incidence of recurrent Clostridioides difficile infections (rCDIs), but prospectively collected safety data needed to broaden patient access and protect public health have been limited. Objectives: We provide cumulative safety data from five prospective clinical trials evaluating fecal microbiota, live-jslm (RBL) – the first microbiota-based live biotherapeutic product approved by the US Food and Drug Administration – for preventing rCDI in adults. Design: Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Both appear to have only mild to moderate gastrointestinal side effects and no major safety events, though post-marketing surveillance is ongoing. 127 , 132 Some patients may be interested in an oral regimen that can be taken discreetly at their home, while others may prefer a one-time treatment in a clinical setting. A recent survey of LBP-naïve subjects with prior CDI showed that 87% were likely to consider a rectally administered treatment and that patients who had received a rectal LBP found it easy, quick, and appealing due to lack of bowel preparation.…”
Section: Clinical Trials Of the Fda Approved Lbps (Rebyota And Vowst)mentioning
confidence: 99%
“…Both appear to have only mild to moderate gastrointestinal side effects and no major safety events, though post-marketing surveillance is ongoing. 127 , 132 Some patients may be interested in an oral regimen that can be taken discreetly at their home, while others may prefer a one-time treatment in a clinical setting. A recent survey of LBP-naïve subjects with prior CDI showed that 87% were likely to consider a rectally administered treatment and that patients who had received a rectal LBP found it easy, quick, and appealing due to lack of bowel preparation.…”
Section: Clinical Trials Of the Fda Approved Lbps (Rebyota And Vowst)mentioning
confidence: 99%
“…A small number of bloodstream infections caused by organisms in FMT have been documented as well (Solari et al, 2014;DeFilipp et al, 2019), however most of such cases have occurred in patients who are immunocompromised and therefore at a high risk of bacterial translocation. In contrast, safety data extracted from LBP trials have revealed a similar frequency of events with the majority being mild to moderate adverse events of similar gastrointestinal nature and thus far there are no reports of infectious diseases being transmitted by LBPs (Lee et al, 2023). Further, controlled clinical trials require more stringent safety reporting, including solicited adverse events and adjudication by independent Drug and Safety Monitoring Boards.…”
Section: Safety Datamentioning
confidence: 99%
“…Rebyota is a rectally administered, pre-packaged, single-dose microbiota suspension of 150 mL. Its effectiveness has been evaluated through randomized, double-blind, placebo-controlled, multicenter studies, demonstrating that Rebyota is well-tolerated and safe for use in adults with rCDI [ 72 , 73 ]. Additionally, the FDA recently approved Vowst as the first orally administered fecal microbiota product for preventing CDI recurrence following antibacterial treatment [ 74 ].…”
Section: Treatment Of C Difficile Infectionmentioning
confidence: 99%